Cultural resources, academic self-concept, and achievement of chemistry students in senior secondary schools of Calabar Municipality, Cross River State, Nigeria - Nja, Cecilia Obi; Ukwetang, John Okpa; Orim, Richard Ekonesi; Neji, Hope Amba; Edu, Grace Onya; Ukah, Julius Ukah; Olofu, Martin Afen (Frontiers in Education, 2022)
This paper investigated cultural resources, academic self-concept, and achievement of chemistry students in a senior secondary school in Nigeria. Research questions and hypotheses were formulated to direct the study. A quasi-experimental factorial design was used in this study, which had a sample size of 90 senior secondary chemistry students. The Academic Self-concept Questionnaire (ASCQ) and Chemistry Achievement Test (CAT) were used in this study. The reliability of ASCQ was done using Cronbach Alpha and it was 0.80 while the reliability of CAT was done using Kuder Richardson formula 20 and had a coefficient of 0.79. The results obtained were analyzed using a dependent t-test and analysis of variance (ANCOVA). Analysis of data showed that the academic self-concept of the students increased after using cultural resources and the experimental group gained more than the control. This study found that cultural resources made the learning of chemical concepts easy to comprehend as the materials were things that the learners were familiar with. This study recommends, among others, that teachers use cultural resources in teaching chemistry.